A modified technique of mega prosthesis revision on non-neoplastic patient: Case report. (October 2020) - Prabowo, Yogi; Ramang, Didi Saputra; Farqani, Syahdi; Arya Mahendra Karda, I Wayan
Abstract: Introduction: Mega prosthesis is mainly used for the treatment of the oncologic patient whose limb underwent salvage surgery that caused the limb to lose significant bone or soft tissue. In recent years, mega prosthesis can also be used to treat non-oncologic patients. Presentation of case: We presented a case of a 40-year-old male with chief complain of pain on the right knee 5 months before admission. Four years previously, the patient sustained motor vehicle accident that fractured his head of femur dan distal femur. He underwent 2-staged surgery for his femoral head and distal femur. However, he presented a year later with signs of non-union and finally underwent mega prosthesis surgery on his distal femur. During his follow up, he experienced a fracture on his prosthesis 3 years later and was referred to our institution. Physical examination shows deformity and slight varus on the right knee, and limited range of motion. The patient then underwent implant revisions. Discussion: After 12 months of post revision surgery follow-up, the patient was able to walk independently. Our patient has not had any sign or episode of failure after the follow up for 12 months. According to literature, the incidence of failure is mostly at 48–72 months post implantation. Conclusion: The problem for this patient maybe caused by the mechanical fatigue of the implant due to stress addressed to the implant. Our current technique of revisions procedure hopefully will enhance the power of the mega prosthesis for further usage. Highlights: Mega prosthesis is mainly used for the treatment of the oncologic patient whose underwent salvage surgery causing the limb to lose significant bone or soft tissue. In recent years, mega prosthesis can also be used to treat non-oncologic patients. Mega prosthesis revision using a modified technique resulted in good functional outcome.